2011
DOI: 10.1504/jgba.2011.040332
|View full text |Cite
|
Sign up to set email alerts
|

Sourcing strategies, practices and effects on organisational performance

Abstract: Today's highly competitive world requires successful businesses to 'reinvent' themselves almost continuously. Manufacturers face tremendous challenges on a variety of fronts. Sourcing has emerged as an integral part of firms' competitive advantage building. One of the distinguishing attributes of effective sourcing strategy is that it plays an integrative role in the firm's strategic planning process. This means firms must have comprehensive strategic decision-making procedures. The study is based on Transacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…So, it suggested that further study can divide the survey instrument to be completed by various department managers separately to avoid respondent bias and measurement error. Many firms have successfully implemented managerial capabilities, technological capabilities, marketing capabilities, competitive priorities, strategic flexibilities and sourcing activities that improve performance (Naqshbandi & Idris, 2012;Parnell, 2011;Hilman & Mohamed, 2011;Gyampah & Acquaah, 2008;Javalgi, Whipple & Ghosh, 2005). However, the questions of how above mentioned strategic factors could well align with Malaysia hotels' business strategies are still vague.…”
Section: Limitations and Future Recommendationsmentioning
confidence: 99%
“…So, it suggested that further study can divide the survey instrument to be completed by various department managers separately to avoid respondent bias and measurement error. Many firms have successfully implemented managerial capabilities, technological capabilities, marketing capabilities, competitive priorities, strategic flexibilities and sourcing activities that improve performance (Naqshbandi & Idris, 2012;Parnell, 2011;Hilman & Mohamed, 2011;Gyampah & Acquaah, 2008;Javalgi, Whipple & Ghosh, 2005). However, the questions of how above mentioned strategic factors could well align with Malaysia hotels' business strategies are still vague.…”
Section: Limitations and Future Recommendationsmentioning
confidence: 99%
“…Research has been conducted on organizational performance and a number of performance measures have been developed (e.g., Kaplan & Norton, 2005; Lebas & Euske, 2006). Some are based on financial measures (e.g., Kamyabi & Devi, 2012; Liao & Wu, 2009) and nonfinancial indicators (e.g., Gronum, Verreynne, & Kastelle, 2012; Hilman & Mohamed, 2011; Kaplan & Norton, 2005; Kirby, 2005) and others are based on the combination of both financial and nonfinancial measures (e.g., Bititci, Carrie, & McDevitt, 1997; Kaplan & Norton, 2005; MacDougall & Pike, 2003). These indicators are developed to serve profit-oriented organization, which could not be appropriate to be applied to organizations in the academia where teaching, community service, research, and publications are the main business.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Allen and Helms (2002) reported that organisational strategy has a positive effect on the performance of an organisation. Additionally, recent literature indicates a positive relationship between strategy and performance (Ajagbe et al, 2016;Hilman and Mohamed, 2011;Hilman and Kaliappen, 2015;Ndubisi et al, 2015;Saffarzadeh and Jandaghi, 2013;Sohail and Ghamdi, 2012).…”
Section: Organisational Strategy and Performance Linkmentioning
confidence: 99%